Reuse of norgestomet implants in an eCG-based superovulation protocol administered to Nelore (Bos taurus indicus) cows - Sudano, Mateus Jose [UNESP]; Landim-Alvarenga, Fernanda da Cruz [UNESP]; Sartori, Roberto; Machado, Rui (Elsevier B.V., 2011)
This study assessed the reuse of norgestomet implants in Nelore cows that were superstimulated with eCG. In a crossover design trial, eight cows were randomly divided into two experimental groups and twice superstimulated: Group 1 - half of the cows received a new norgestomet implant and 2 mg estradiol benzoate (EB) on Day 0; Group 2 - remaining cows received two once-used norgestomet implants and 2 mg EB also on Day 0. on Day 4 all cows received a single dose of 2000 IU eCG, and on Day 6 cows were treated with two doses of PGF(2 alpha), 12 h apart. Ovulation was induced with 12.5 mg pLH 12 h after implant withdrawal (on Day 7), and fixed-time artificial inseminations were carried out 12 and 24 h later. Seven days after pLH injection embryos were recovered and blood samples were taken to determine circulating progesterone. Ultrasound examinations were performed at pLFI administration and at embryo recovery. The number of large follicles (>= 8 mm) was greater (P<0.05) in Group 1(17.1 +/- 1.8) than in Group 2 cows (9.7 +/- 1.6). The mean number of corporalutea was greater (P<0.05) for Group 1(13.8 +/- 1.8) as compared to Group 2 cows (5.4 +/- 1.0) and the percentage of large follicles that ovulated following pLH administration also differed (P<0.05) between treatments (80.3% and 53.8% for cows in Groups 1 and 2, respectively). However, no differences (P>0.05) were found between treatments (respectively, for Group 1 and Group 2 cows) in the follicle diameter (10.5 +/- 1.6 and 102 +/- 1.7 mm), corpus luteum (CL) diameter (15.7 +/- 1.8 and 14.4 +/- 1.7 mm), CL volume (2232 1356 and 1893 +/- 1828 mm(3)), ova/embryos recovered (6.3 +/- 1.1 and 4.0 +/- 1.9), transferable embryos (4.0 +/- 1.8 and 2.5 +/- 1.0) and plasma progesterone concentration (36.1 +/- 83 and 35.1 +/- 6.9 ng/mL). In conclusion, the stimulatory effects on the ovaries provided by the use of two once-used implants were less intense than the ones verified after using a new implant. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Norgestomet; Superovulation; eCG; Nelore; Bos taurus indicus